A novel method for quantifying the amount of trabecular meshwork pigment in glaucomatous and nonglaucomatous eyes - Kinori, Michael; Hostovsky, Avner; Skaat, Alon; Schwartsman, Jonathan; Melamed, Shlomo (Journal of glaucoma, 2014)
To assess the use of a computerized program for evaluating the amount of trabecular meshwork (TM) pigmentation in normal (control), primary open-angle glaucoma (POAG), and pseudoexfoliation glaucoma/pigmentary dispersion glaucoma (PXFG/PDG) patients. All included patients were from the Goldschleger Eye Institute glaucoma clinic. After signing an informed consent, each patient's anterior chamber angle was photographed using a single photo-slit under the same conditions. Only one eye per patient was photographed. The superior TM and the inferior TM were documented. Then, the degree of "blackness" (representing melanin pigment) was assessed using the ImageJ program. Of the 43 eyes photographed, 8 were excluded because of low-quality images. Of the remaining 35 patients, 14 were normal, 10 had POAG, and 11 had PXFG/PDG. The amount of pigment was the same in the control and the POAG patients whether the inferior TM (P=0.24), superior TM (P=0.58), or the sum inferior TM+superior TM (P=0.85) was measured. The pigment level was significantly higher in the PXFG/PDG group than in the control group (inferior TM, P<0.01; superior TM, P=0.047; sum, P<0.01). The difference between the inferior and the superior TM pigment levels was found to be statistically insignificant in all the groups (normal, P=0.86; POAG, P=0.10; PXFG/PDG, P=0.22). The use of ImageJ software might play a role in the quantification of pigment evaluation of the TM.